2019
DOI: 10.1002/rcm.8507
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐fast retroactive processing of liquid chromatography high‐resolution full‐scan Orbitrap mass spectrometry data in anti‐doping screening of human urine

Abstract: Rationale Retroactive analysis of previously tested urine samples has become an important sports anti‐doping tool. Retroactive reprocessing of old data files acquired from a generic screening procedure can reveal detection of initially unknown substances, like illegal drugs and newly identified metabolites. Methods To be able to efficiently search through hundreds to thousands of liquid chromatography high‐resolution full‐scan Orbitrap mass spectrometry data files of anti‐doping samples, a combination of MetAl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Overall, the GC‐Q/Orbitrap data were described as superior but both systems were found fit‐for‐purpose in anti‐doping analysis, and the employed full scan HRMS measurements also allowed for data reprocessing where desirable. Proof‐of‐concept concerning the retroactive analysis of datasets (and corresponding long‐term stored urine samples) was provided by Lommen et al, who demonstrated the practicality of data reduction and subsequent automated evaluation . Employed in the context of screening ITP data, false‐negative results were virtually excluded and algorithm settings tailored to individual analytes allowed for reducing the frequency of false warnings to an acceptable minimum.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…Overall, the GC‐Q/Orbitrap data were described as superior but both systems were found fit‐for‐purpose in anti‐doping analysis, and the employed full scan HRMS measurements also allowed for data reprocessing where desirable. Proof‐of‐concept concerning the retroactive analysis of datasets (and corresponding long‐term stored urine samples) was provided by Lommen et al, who demonstrated the practicality of data reduction and subsequent automated evaluation . Employed in the context of screening ITP data, false‐negative results were virtually excluded and algorithm settings tailored to individual analytes allowed for reducing the frequency of false warnings to an acceptable minimum.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…[7][8][9][10] MetAlign has been studied in Anti-Doping Lab Qatar (ADLQ) for Orbitrap LC/HR-FS-MS data processing. 11 MetAlign performs datafile digital information reduction and subsequently searches for substances using the HR_MS_search module. MetAlign has the potential to be used as an antidoping tool for preventive and fast retroactive reprocessing of old datafiles for the discovery of designer drugs or new long-term metabolites for prohibited substances without reporting limits, like anabolic androgenic steroids (AAS), as defined in the WADA Technical Document for the Minimum Required Performance Limits (MRPL).…”
Section: Introductionmentioning
confidence: 99%
“…Cheng, and Asarum heterotropoides F. Schmidt 9 , as well as in S. acutum stem. Coclaurine could also be a potential stimulant because it is a metabolite of higenamine with a similar chemical structure 10 12 . Coclaurine has also been identified in rat urine by gas chromatography/mass spectrometry after higenamine administration 13 .…”
Section: Introductionmentioning
confidence: 99%